Certain convex harmonic functions - Yong Chan Kim; Jay M. Jahangiri; Jae Ho Choi (International Journal of Mathematics and Mathematical Sciences)
We define and investigate a family of complex-valued harmonic convex univalent functions related to uniformly convex analytic functions. We obtain coefficient bounds, extreme points, distortion theorems, convolution and convex combinations for this family.